A Geochemical Overview of Mid-Archaean Metavolcanic Rocks from Southwest Greenland - Kristoffer Szilas (Geosciences, 2018)
The present contribution reviews bulk-rock geochemical data for mid-Archaean (ca. 3075–2840 Ma) metavolcanic rocks from the North Atlantic Craton of southwest Greenland. The data set includes the most recent high quality major and trace element geochemical analyses for ten different supracrustal/greenstone belts in the region. When distilling the data set to only include the least altered metavolcanic rocks, by filtering out obviously altered samples, mafic/ultramafic cumulate rocks, late-stage intrusive sheets (dolerites) and migmatites, the remaining data (N = 427) reveal two fundamentally distinct geochemical suites. The contrasting trends that emerge from the filtered geochemical data set, which best represents the melt compositions for these mid-Archaean metavolcanic rocks are: (1) tholeiitic (mainly basaltic) versus (2) calc-alkaline (mainly andesitic). These two rock suites are effectively separated by their La/Sm ratios (below or above three, respectively). It is demonstrated by geochemical modelling that the two contrasting suites cannot be related by either fractional crystallization or crustal assimilation processes, despite occurring within the same metavolcanic sequences. The tholeiitic basaltic rocks were directly mantle-derived, whereas the petrogenesis of the calc-alkaline andesitic rocks involve a significant (>50%) felsic component. The felsic contribution in the calc-alkaline suite could either represent slab-melt metasomatism of their mantle source, mafic-felsic magma mixing, or very large degrees of partial melting of mafic lower crust. At face value, the occurrence of andesites, and the negative Nb-Ta-Ti-anomalies of both suites, is consistent with a subduction zone setting for the origin of these metavolcanic rocks. However, the latter geochemical feature is inherent to processes involving crustal partial melts, and therefore independent lines of evidence are needed to substantiate the hypothesis that plate tectonic processes were already operating by the mid-Archaean.